STRUCTURAL CHANGES IN THE TOURIST INDUSTRY - Rossana Galdini (European Regional Science Association (ERSA), 2005)
The paper analyzes the role and the significance of tourism, as one particular set of industries that are of great significance in contemporary western societies, namely consumer services and especially tourist- related services. Particular emphasis is given to the impact of tourism on host communities, the changing role of tourism in the European economy, the relationship between tourism and environment, and its place in urban regeneration. Tourism is one of the most significant social forces in the world today. It also has enormous international economic and geopolitical importance. The economic, social environmental and cultural implications of such developments can be seen in a lot of cities. Tourism constructs, rearranges, and inhabits geographic, social and cultural spaces globally. This paper tries to better understand in a systematic way the spatial relationships, tourism systems and environments.The focus is on consumption and culture as drivers of urban policy. The main theme is that of tourism as a totalizing social construction of places and identities. The strong connections between society, time and space implies that the concept of 'society', the nature of 'locality', the significance of 'economic restructuring', and the concept of the 'rural', are to be examined in relationship to place. The paper then considers how places have been transformed by the development of service occupations and industries. Attention is then devoted to the ways in which places are consumed, the visual character of such consumption and its implications for place and people. The implications for nature and the environment are also explored . Places are constructed for tourism consumption through the promotion of certain images that have implications for the built environment. Tourist consumption is a place- creating and a place-altering act. The production and expansion of tourist spaces has consequences for the build environment, and so the promotion of a certain images can impact on the authenticity of environments. The paper tries to provide a critical approach of how places of cultural significance are trasformed into places of consumption by investigating the relationship between culture as a resorce for identity and social meaning and culture as an important economic resource for post-industrial cities.
Keywords: 330